Spatial Analysis of Flood Hazard in Nirchay River Basin Using HEC-HMS Model and and fuzzy logic - fariba sfandyary darabad; mansour kheirizade; masoud rahimi (تحقیقات کاربردی علوم جغرافیایی)
Floods are one of the most abundant and destructive natural disasters that every year are caused heavy losses of life and property. Due to human activity in river systems and construction in rivers, flood damage has an upward trend. One of the most important actions to reduce flood damage is the provision of flood hazard zoning maps and their use in spatial planning. In this study, the risk of flood in the Nirchay River Basin that located Ardebil province was investigated. For this purpose, the HEC-HMS model was used to simulate rainfall-runoff and to identify flood zones and fuzzy logic in order to overlay the layers and prepare a flood hazard zoning map.The simulation results show the high performance of the HEC-HMS model in simulating rainfall-runoff of the Nirchay River Basin and estimating peak flood discharges. Rainfall conversion to runoff at the Nirchay River Basin controlled by slope and land-use.The most runoff height and peak flow in Nirchay River Basin are located in the upstream sub-basins. This is due to the steep, low permeability soil, frequency impervious surfaces and high CN. The combination of layers using fuzzy logic has shown that about 8.6% of the surface of the basin are located with a high risk of flooding. These zones are located mainly on the floodplain of the Nirchay Basin. Due to the Low valley width and low slope, these lands are always at flood risk. Most settlements in the study area are located at downstream of the basin. This has increased the risk of flooding.